Effect of cleaner fish on sea lice in Norwegian salmon aquaculture: a national scale data analysis. Issue 10 (September 2020) - Barrett, Luke T.; Overton, Kathy; Stien, Lars H.; Oppedal, Frode; Dempster, Tim
Graphical abstract: Highlights: The use of cleaner fish was not correlated with sea louse infestation density. Farms that used many cleaner fish were able to wait longer before delousing. Stocking cleaner fish slowed sea louse population growth over the next 12 weeks. Effects were highly variable, resulting in weak effects when viewed at a national scale. Abstract: The salmon aquaculture industry has adopted the use of invertivorous 'cleaner fishes' (CF) for biological control of sea louse infestations on farmed salmon. At present, 50 million CF are used annually in Norway alone, with variable success in experimental and industrial contexts. We used a national scale database of louse counts, delousing treatments and CF stocking events on Norwegian salmon farms to test for evidence of CF efficacy at 488 sites that completed a grow-out cycle within 2016–2018. Our analysis revealed that sites using more CF over the duration of a grow-out cycle did not have fewer lice on average, likely because CF use is reactive and in proportion to the scale of the louse problem. Over time within sites, we found that (i) sites using more CF early in the grow-out cycle were able to wait slightly longer (conservatively, a 5.2 week delay with 5000 CF stocked week −1 ) before conducting the first delousing treatment, and (ii) CF stocking events were followed, on average, by a small reduction in louse population growth rates. However, both effects were small and highly variable, and louse population growth rates remained positive on average, even when large numbers of CF were used (tens of thousands per site). Moreover, effects of CF on louse density tended to be short-lived, likely reflecting mortality and escape of stocked CF. Overall, the data indicate that while some sites consistently obtain good results from CF, there is also widespread suboptimal use. A better understanding of factors affecting CF efficacy in commercial sea cages is required to inform legislation and drive more efficient and ethical use of CF by the salmon aquaculture industry.